The Relationship between Post-Pandemic Organizational Climate and Teacher Performance in Public Elementary Schools - Kusumaningrum, Desi Eri; Teguh Triwiyanto; Bambang Budi Wiyono; Raden Bambang Sumarsono; Firda Fitrotul Unsa; Arumia Fairuz Husna; Sasi Maulina; Warapark Maitreephun; Erika Mei Budiarti; Suwandi (LPPM Undiksha, 2024)
The background of this study is the comprehensive changes in social life due to the COVID-19 pandemic outbreak, which is assumed to affect many aspects of the education sector. This study analyses the relationship between two selected variables: organizational climate and teacher performance in public primary schools after the COVID-19 pandemic. This research is a quantitative study with a correlational research design. Data was collected using a closed questionnaire distributed to 128 primary school teacher respondents. The instrument used was a questionnaire sheet. The number of respondents obtained by researchers is determined through cluster sampling techniques, also known as cluster sampling techniques. The results showed a significant and simultaneous relationship between organizational climate and teacher performance in public elementary schools with an extreme category relationship level. Thus, the post-pandemic organizational climate significantly correlates with teacher performance in public primary schools after the COVID-19 pandemic. The results of this study can also be used as a basis for further research to analyze differences in two periods with the same variables.